"Jorrar água sobre esta cidade": uma história ambiental do saneamento em Caxias do Sul (1875 -1928) - Troglio, Lucas (My University, 2021)
The issue of sanitation and its environmental implications is one of the most urgent and poorly resolved in Brazil, so that a large part of the population still does not have access to this essential service and its absence, or poor management, produces significant socioenvironmental impacts. The objective of this dissertation is to understand the implementation of sanitation services, from its human and non-human actors, in Caxias do Sul between the years 1875 and 1928, and to produce a short documentary that narrates part of this dynamic. The research was carried out using the documentation, text and images, produced by the Municipal Intendency and the press of the period. Bruno Latour's actor-network theory was the key to understanding the collective of human and non-human actors in association with sanitation and public hygiene practices. It was possible to verify the expansion of this collective and a series of landscape transformations resulting from the implementation of sanitation technologies, the increase in demographic density and the establishment of microorganisms that cause some diseases related to this process. Regarding the production of the documentary, was verified the relevance of the themes related to Environmental History and Environmental Education in History Teaching, as well as the importance of Public History and History Dissemination practices in order to expand the public and the social impact of researches in History. [resumo fornecido pelo autor]
A questão do saneamento e suas implicações ambientais é uma das mais urgentes e mal resolvidas no Brasil, de forma que grande parte da população ainda não tem acesso a esse serviço essencial e sua ausência, ou má administração, produz significativos impactos socioambientais. O objetivo desta dissertação é compreender a implantação dos serviços de saneamento, a partir de seus atores humanos e não humanos, em Caxias do Sul entre os anos de 1875 e 1928, e produzir um documentário de curta-metragem que narre parte dessa dinâmica. A pesquisa foi realizada a partir das documentações, textuais e de imagens, produzidas pela Intendência Municipal e a imprensa do período. A teoria do ator-rede de Bruno Latour foi a chave de leitura para o entendimento do coletivo de atores humanos e não humanos em associação nas práticas de saneamento e higiene pública. Foi possível verificar a expansão desse coletivo e uma série de transformações da paisagem decorrentes da implantação de tecnologias de saneamento, do aumento da densidade demográfica e o estabelecimento de microrganismos causadores de algumas doenças relacionadas a esse processo. Sobre a produção do documentário, verificou-se a pertinência dos temas relacionados à História Ambiental e Educação Ambiental no Ensino de História, assim como a importância de práticas de História Pública e Divulgação de História na intenção de ampliar o público e o impacto social das pesquisas em História. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Saneamento - Caxias do Sul, RS - História; Meio ambiente - História; Documentário (Cinema); História pública; History - Study and teaching; Sanitation - Caxias do Sul, Brazil - History; Environment - History; Documentary films; Public history